The Role of Internal Audit in Fraud Detection and Prevention: A Multi-Contextual Review and Research Agenda - Oyedotun, Samuel Abiodun; Oise, Godfrey Perfectson; Akilo, Babalola Eyitemi; Nwabuokei, Onyemaechi Clement; Ejenarhome, Prosper Otega; Fole, Mary; Onwuzo, Chioma Julia (Journal of Science Research and Reviews, 2025)
This review examines the critical role of internal audit in fraud detection and prevention across various organizational and national contexts. Drawing on over 30 studies published between 2000 and 2024, it identifies key audit attributes, independence, competence, objectivity, and professional skepticism, that significantly aid in mitigating fraud. The paper traces the evolution of internal audit from a compliance tool to a strategic function supporting governance, risk management, and financial transparency. Despite broad recognition of internal audits, the literature reveals several limitations. Most studies focus on developing countries such as Indonesia, Nigeria, and Pakistan, and are concentrated in the public and financial sectors. Methodologically, reliance on cross-sectional and survey-based research limits understanding of the dynamic nature of fraud and the long-term effects of audit interventions. Key underexplored areas include the adoption of emerging technologies (e.g., AI, blockchain, big data analytics), the role of organizational culture and leadership ethics, and challenges faced by Small and Medium Enterprises (SMEs), which often lack formal controls. The review also notes an over-reliance on traditional theoretical frameworks like agency theory and COSO, which inadequately address behavioral and sociological aspects of fraud. To address these gaps, the paper proposes a future research agenda that includes comparative and cross-cultural studies, longitudinal and mixed-method designs, and interdisciplinary approaches that integrate ethics and technology. Greater attention to underrepresented sectors such as SMEs and nonprofits is also recommended. Ultimately, the study advocates for continuous innovation in internal audit practices to meet evolving fraud risks and governance demands in a digital, globalized environment. Bridging current gaps can enhance both academic understanding and practical implementation, fostering more resilient and accountable organizations.
Keywords: Auditor Attributes; Audit Effectiveness; Emerging Markets; Fraud Detection; Fraud Prevention; Internal Audit; Risk Management